  # Ken Ward's Mathematics Pages

## Trigonometry Cosine, Sine and Tangent of Multiple Angles (Chebyshev's Method)

Whilst De Moivre's Theorem for Multiple Angles enables us to compute a sine or cosine of a multiple angle directly, for the cosine we need to convert powers of sine to cosines (and similarly for the sine). However, Chebyshev's Method gives the formula in the required form for the cosine, and, for sines, requires the conversion of cosine squared to sines only (as opposed to converting higher powers using DeMoivre). However, there is an algorithm which does this more directly. Computing the tangents can become complicated, as n increases, so the method for tangents is particularly valueable. I refer to the method as Chebyshev's Method, because Pafnuty Chebyshev (Tchebysheff) (1821-1894), a Russian Mathematician, certainly knew this formula (and for any later reference, it is better to give it some name!). This is a recursive method.

Trigonometry Contents

## Chebyshev Method

We compute the cosine for nx from the cosines of (n-1) and (n-2) as follows: [1.1]

Similarly we compute the sine of nx from the sines of (n-1)x and (n-2)x [1.2]

For the tangent, we have: [1.3]
where H/K=tan (n-1)x

## Examples

### Cosine

Starting from cos(1·x)=cos x, and cos2x=2cos2x-1, using formula 1.1, we can compute
cos 3x=2cos x(2cos2x−1)−cos x
=4·cos3x−2·cos x−cos x
=4·cos3x−3·cos x

### Sine

Starting from sin(1·x)=sin x, and sin2x=2·sin x·cos x, using formula 1.2, we can compute
sin 3x=2·cos x·(2·sin x·cos x)−sin x
=4·cos2x·sin x−sin x
=4·(1−sin2x)·sin x−sin x
=3·sin x−4sin3x

### Tangent

If we wish to find tan2x; that is the multiple angle formula for the tangent when n=2,  and we know tan (n-1)x=tan x. Therefore n=2, H=tan x, and K=1, using formula 1.3, reproduced below: [1.3]
And substituting our values, we find:
tan 2x=(tan x+tan x·1)/(1-tan x·tan x)
=2·tan x/(1-tan2x)

If we continue, with n=3, H=2·tan x, K=1−tan2x, using the formula we have:
tan 3x=(2·tan x+tan x·(1−tan2x))/(1−tan2x−(2·tan x)tan x)

=(3·tan x−tan3x)/(1−3·tan2x)

This formula uses the previous term only (as apposed to the previous two terms for the sine and cosine formulae).

## Proof

That we have chosen to claim to prove the formula for all integers, n, neither implies nor does not imply the truth of the equations for rational, real or complex numbers.

### Cosine

We wish to prove that: [1.1, repeated]
for all integers, n.

To do this we use the compound angle formula to show that the right-hand side of Equation 1.1 is actually cos(nx).

Expanding the right-hand side, using the compound angle formula for sine and cosine:
cos nx=[2·cos(nx)cos (x) + 2·sin(nx)sin x]·cos (x)−[cos(nx)cos2x+sin(nx)sin2x]

Writing cos2x as 2·cos2x−1, and sin2x as 2·sin x·cosx, and multiplying out some brackets:
=2·cos(nx)cos2(x)+ 2·sin(nx)sin x·cos (x)−cos(nx)·(2·cos2x−1)−sin(nx)·2·sinx·cosx

Multiplying out further brackets
=2·cos(nx)cos2(x)+ 2·sin(nx)sin x·cos (x)−2·cos(nx)·cos2x+cos(nx)−2·sin(nx)·sinx·cosx

Grouping similar terms, most of which cancel:
=cos(nx)

### Sine

We wish to prove that: [1.2, repeated]
for all integers n.

Expanding the right-hand side of Equation 1.2, using the compound angle formula for sine and cosine:
sin nx=[2·sin(nx)cos (x) + 2·cos(nx)sin x]·cos (x)−[sin(nx)cos2x+cos(nx)sin2x]

Writing cos2x as 1−2·sin2x, and sin2x as 2·sin x·cosx
=[2·sin(nx)cos (x) + 2·cos(nx)sin x]·cos (x)−sin(nx)(1−2·sin2x)−2·sin x·cos x·cos(nx)
=2·sin(nx)cos2 (x)+ 2·cos(nx)sin x·cos (x)−sin(nx)+2·sin2x·sin(nx)−2·sin x·cos x·cos(nx)

Writing cos2 (x) as 1−sin2 x)
=2·sin(nx)(1−sin2 x)+ 2·cos(nx)sin x·cos (x)−sin(nx)+2·sin2x·sin(nx)−2·sin x·cos x·cos(nx)

Multiplying out brackets:
=2·sin(nx)−2·sin(nx)·sin2 x+ 2·cos(nx)sin x·cos (x)−sin(nx)+2·sin2x·sin(nx)−2·sin x·cos x·cos(nx)

Grouping similar terms (most cancelling):
=sin (nx)

Therefore the left-hand side of Equation 1.2 equals the right-hand side: [1.2, repeated]

### Tangent

We note from the compound angle formula for the tangent: [3.1]

because tan nx=tan[(n-1)x+x]: [3.2]
If we let: [3.3]
where H is the dividend (top bit) and K is the divisor (bottom bit) of the expression for the tangent.

Substituting 3.3 in 3.1, we get: [3.4]

And multiplying top and bottom by K becomes our recursive formula: The tangent formula produces the current formula using only the previous formula, unlike sine and cosine which require two previous formula.

Trigonometry Contents

Ken Ward's Mathematics Pages

# Faster Arithmetic - by Ken Ward

Ken's book is packed with examples and explanations that enable you to discover more than 150 techniques to speed up your arithmetic and increase your understanding of numbers. Paperback and Kindle: 